Clamping Angle Control PWM Method to Restore Linear Modulation Range of a Voltage Source Inverter - Kim, Jae Goo; Lee, Kyo Beum; Park, Jung Wook (IEEE Transactions on Power Electronics, 2018)
This paper proposes the new clamping angle control (CAC) pulse width modulation (PWM) method to restore its maximum linear modulation range of voltage source inverters (VSIs) reduced by the duty ratio limitation in hardware implementation, which makes the VSIs to operate nonlinearly in the high modulation range. The deadtime and the bootstrap gate driver circuit mainly cause this duty ratio limitation in practice. In particular, the bootstrap gate driver circuit is used in many industrial applications by avoiding the additional power supply to apply the gate-source voltage of power switches, and therefore making the VSIs to be small size with the low cost. First, the proposed CACPWM method is theoretically analyzed. Then, it is applied in the high modulation range to overcome the limitation of the duty ratio due to the use of the bootstrap gate driver circuit. Thereafter, its practical effectiveness is verified by both simulation and experimental tests. Also, the resulting harmonic distortions are compared with those by the conventional PWM methods.
Keywords: Angle control; Duty ratios; Gate driver circuit; Linear modulations; Space vector pulse width modulation; Voltage source inverter; Bootstrap gate driver circuit; clamping angle control (CAC); duty ratio; linear modulation range; pulse width modulation (PWM); voltage source inverter (VSI)